Histochemical study of muscle fiber types in Synbranchus marmoratus Bloch, 1795 - Dal Pai-Silva, Maeli [UNESP]; Dal Pai, Vitalino [UNESP]; Da Mota, Diogenes Luiz [UNESP]; De Castro Rodrigues, Antonio [UNESP] (Elsevier, 1996)
The myotomal muscle of Synbranchus marmoratus was investigated using histochemical and immunohistochemical reactions. This musculature is composed of a superficial red compartment, uniformly distributed around the trunk circumferentially and also in the lateral line. The red compartment fibers are small in diameter and have an oxidative metabolism, a high rate of glycogen and a negative reaction to alkaline and acid myofibrillar ATPase (mATPase). The white muscle forms the bulk of the muscle mass. Its fibers are large in diameter and have a glycolytic metabolism, a negative reaction to glycogen, a strong reaction to alkaline mATPase and a negative reaction to acid mATPase. Between these two compartments there is an intermediate layer of fibers presenting a mosaic metabolism pattern with a high rate of glycogen. These fibers stained moderately for alkaline and acid m-ATPase. Several clusters of red muscles were observed inside the white muscle. Each cluster is composed of three fiber types, with a predominance of red and intermediate fibers. Reactivity to anti-MHC BA-D5 was positive only in the intermediate fibers. Reactivity to anti-MHC SC-71 was negative in all fiber types.
Keywords: Enzyme histochemistry; Fish; Immunohistochemistry; Muscle fiber types; Synbranchus marmoratus; adenosine triphosphatase; aerobic metabolism; animal cell; fast muscle fiber; fish; glycogen metabolism; histochemistry; immunohistochemistry; muscle cell; muscle metabolism; nonhuman; slow muscle fiber; Adenosine Triphosphatases; Animals; Body Weight; Dihydrolipoamide Dehydrogenase; Fishes; Glycogen; Glycolysis; Histocytochemistry; Muscle Fibers; Muscle Fibers, Fast-Twitch; Muscle, Skeletal; Myofibrils